2012
DOI: 10.1051/0004-6361/201118187
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the temperature dependence of the in-medium nucleon mass on core-collapse supernovae

Abstract: Aims. A complete description of the core collapse supernova mechanism requires an appropriate treatment of both the hydrodynamics and the microphysics. We study the influence of a nuclear physics input, namely the temperature dependence of the nucleon effective mass in nuclei induced by the in-medium effects, in the core collapse of a massive star. Methods. We present here the first implementation of this nuclear input in a hydrodynamical one-dimensional simulation. The simulations are performed with a spheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In both cases, the surface and bulk properties of nuclei are modified as compared to the vacuum at zero temperature. One aspect is a temperature dependence of the symmetry energy (Dean, Langanke, and Sampaio, 2002;Agrawal et al, 2014) and of effective nucleon masses (Donati et al, 1994;Fantina et al, 2012). Obviously, such temperature effects are related to excited states and internal partition functions but the problem is approached from a different perspective.…”
Section: Medium Modifications Of Heavy Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, the surface and bulk properties of nuclei are modified as compared to the vacuum at zero temperature. One aspect is a temperature dependence of the symmetry energy (Dean, Langanke, and Sampaio, 2002;Agrawal et al, 2014) and of effective nucleon masses (Donati et al, 1994;Fantina et al, 2012). Obviously, such temperature effects are related to excited states and internal partition functions but the problem is approached from a different perspective.…”
Section: Medium Modifications Of Heavy Nucleimentioning
confidence: 99%
“…This is important for detailed predictions of NS radii and for dynamical properties. Only few such unified NS EoSs exist, see, e.g., Douchin and Haensel (2001); Fantina et al (2013); Miyatsu et al (2013); Baldo et al (2014); Gulminelli and Raduta (2015). Unified NS EoSs can also be obtained from the general purpose EoS, which will be discussed in Sec.…”
Section: Neutron Star Crust Eoss and Unified Neutron Star Eossmentioning
confidence: 99%
“…Indeed, mean field theories predict an average effective mass m * /m around 0.6-0.8 (see, e.g., Bender et al [27] for a review, and references therein). It has been shown that the inclusion of a temperature-dependent nucleon effective mass in nuclei, coming from dynamical correlations beyond mean field, may affect the core-collapse dynamics [28][29][30]. However, as mentioned earlier the details of the nuclear part are not the aim of the present work, and we keep the original version of Lattimer and Swesty [3].…”
Section: A Characteristics Of the Lattimer And Swesty Equation Of Statementioning
confidence: 99%
“…They play, for instance, an important role in predicting β decay halflives of neutron rich nuclei involved in the r-process of the nucleosynthesis [7]. In core-collapse supernova, the GT transitions of pf-shell nuclei give an important contribution to the weak interaction decay rates that play an essential role in the core-collapse dynamics of massive stars [8][9][10]. The neutrino-induced nucleosynthesis may take place via GT processes in neutron-rich environment [11].…”
Section: Introductionmentioning
confidence: 99%